Research on the path of digital economy to solve the fairness and efficiency problems of Chinese modernization - Li, Daohui (International Journal of Emerging Trends in Social Sciences, 2023)
First of all, the research purpose of this paper is to solve the problem of the lack of Chinese-style modernization theory in the process of the coordinated development of efficiency and equity in the development of China's digital economy. Secondly, this paper mainly uses analogical reasoning and literature research. In the first step, by summarizing and comparing the economic theories used by Chinese researchers in the past to solve the problems of China's economic development, the problem of the lack of Chinese-style modernization theory is found. In the second step, this paper deduces the theoretical hypothesis of "synergistic cycle perpetuity theory" by collating and modifying Muir dahl's cyclic accumulation theory and David Harvey's three-level capital cycle theory. Finally, through the research of this paper, it is found that the theory of "collaborative cycle sustainability theory" hypothesis can adapt to the characteristics of the digital economy, and then effectively promote the coordinated development of efficiency and equity, which is helpful to solve the problem of equity imbalance that has emerged in the early industrial economy era of China.